Concept «EDUCATION» and its Subconcepts in the Consciousness of Ukrainian managers - Наталія Михальчук; Наталія Харченко; Георгій Калмиков; Ернест Івашкевич; Едуард Івашкевич; Наталія Хупавцева; Інна Мисан (Психолінгвістика)
The purpose of the research was to describe the meanings of the concept EDUCATION, actualized in the semantic field of linguistic consciousness of managers, who connect their professional activity with IT-technologies.